Explaining adherence to self‐care behaviours amongst adolescents with food allergy: A comparison of the health belief model and the common sense self‐regulation model. (12th February 2013) - Jones, Christina J.; Smith, Helen E.; Frew, Anthony J.; Toit, George Du; Mukhopadhyay, Somnath; Llewellyn, Carrie D.
<x xml:space="preserve">Abstract</x> Objectives To identify explanations for adherence to self‐care behaviours amongst adolescents with food allergy–induced anaphylaxis using two social cognition models: the health belief model (HBM) and the common sense self‐regulation model (CS‐SRM). Design Cross‐sectional self‐completion questionnaire study to gain initial evidence of the two models' feasibility/effectiveness in explaining adherence in an adolescent food‐allergic population. Methods Participants aged 13–19 years with a diagnosis of severe food allergy and a prescription of an adrenaline auto‐injector were recruited from hospital outpatients. Adherence to self‐care behaviours was measured in addition to constructs from the HBM and CS‐SRM. Results One hundred and eighty‐eight food‐allergic adolescents completed the questionnaire. The HBM, specifically the constructs perceived severity and barriers, accounted for 21% of the explained variance in adherence behaviours. CS‐SRM constructs, illness identity, timeline cyclical beliefs and emotional representations explained 25% of the variance. Conclusions Both models performed similarly in explaining adherence to self‐care behaviours in adolescents with food allergy. Interventions designed to elicit personal barriers to adherence and to address perceptions of severity and the unpredictable nature of symptoms may be more effective in improving adherence to self‐care behaviours than current interventions. Statement of contribution What is already known on this subject? Patients' poor management of food allergy induced anaphylaxis is commonly attributed to lack of knowledge and ability in using the adrenaline auto‐injector. Adherence to recommended preventive self‐care behaviours, like allergen avoidance and carrying emergency medication, are rarely assessed. Social Cognition Models (SCMs) have been successfully applied to a number of adherence‐related studies in disease conditions such as asthma and diabetes, but have not yet been applied to food allergy induced anaphylaxis. What does this study add? This is the first large‐scale quantitative study of adherence behaviours in adolescents with food allergy. This is the first study to apply theoretical models to explain adherence in the adolescent food allergic population. This is the first application of both models to food allergy, and the first to compare the two models' measurement instruments.